3D geovisualisation techniques applied in spatial data mining - Valêncio, Carlos Roberto [UNESP]; Kawabata, Thatiane [UNESP]; De Medeiros, Camila Alves [UNESP]; De Souza, Rogéria Cristiane Gratão [UNESP]; Machado, José Márcio [UNESP] (Springer Nature, 2013)
The increase in the number of spatial data collected has motivated the development of geovisualisation techniques, aiming to provide an important resource to support the extraction of knowledge and decision making. One of these techniques are 3D graphs, which provides a dynamic and flexible increase of the results analysis obtained by the spatial data mining algorithms, principally when there are incidences of georeferenced objects in a same local. This work presented as an original contribution the potentialisation of visual resources in a computational environment of spatial data mining and, afterwards, the efficiency of these techniques is demonstrated with the use of a real database. The application has shown to be very interesting in interpreting obtained results, such as patterns that occurred in a same locality and to provide support for activities which could be done as from the visualisation of results. © 2013 Springer-Verlag.
Keywords: Database; Geographic Information System; Geovisualisation; Spatial Data Mining; 3d graphs; Computational environments; Real database; Spatial data; Spatial data mining; Algorithms; Database systems; Geographic information systems; Learning systems; Pattern recognition; Three dimensional; Data mining